Pengaruh Pemahaman Akuntansi dan Pemahaman Perpajakan terhadap Kepatuhan Wajib Pajak pada KPP Pratama Madiun - Trihatmoko, Huda; Mubaraq, Muhammad Raihan (E-Jurnal Akuntansi, 2020)
The research aims to provide empirical evidence of the influence understanding of accounting and understanding of taxation on taxpayer compliance. Measurement of variables in this study using a Likert scale from scale 1 to strongly disagree to scale 4 to strongly agree. The sample in this study was 112 individual taxpayers in KPP Pratama Madiun. Sampling refers to the Slovin formula with a purposive sampling method and analyzed using multiple linear regression. The results of this study indicate that the understanding of accounting has no effect on taxpayer compliance while understanding of taxation has an effect on taxpayer compliance. Keywords: Understanding of Accounting; Understanding of Taxation; Taxpayer Compliance.